Spontaneous splenic infarction in an elderly cirrhotic patient with multiple comorbidities - Elife ERARSLAN; Alper BOZKURT; İlhami YÜKSEL and Hanzade Duygu DEMİR (Turkish Journal of Gastroenterology, 2019)
-